Do northwestern and southeastern Europe share a common ‘cycling mindset’? Comparative analysis of beliefs toward cycling in the Netherlands and the Balkans - Pojani, Dorina; Bakija, Dukagjin; Shkreli, Entela; Corcoran, Jonathan; Mateo-Babiano, Iderlina (European journal of transport and infrastructure research, 2017)
Employing the theory of planned behavior for guidance, this study explores the similarities and differences in beliefs about the decisions to commute by bicycle to work in three small, cyclingoriented cities: Gouda (The Netherlands), Shkodra (Albania), and Peja (Kosovo). The setting in the Balkan Peninsula, a less developed region of Europe which has been more rarely the subject of scientific inquiry, has the potential to offer applicability to (smaller) developing cities. The study identifies the following themes or beliefs related to cycling: (1) health and exercise (2) environment (3) safety (4) enjoyment (5) convenience and practicality (6) financial savings (7) pride and tradition (8) status and image and (9) female independence. The findings suggest that, in developing cities changes to the physical environment alone – although crucial - are likely to be insufficient if travel modes are to shift toward active transport. To this end attitudes and perceptions need to be tackled as well. In promoting cycling, policy makers need to strike a fine balance between the concept of the bicycle as an economical mode and as a “trendy” one. The most promising way forward appears to be a combination of public infrastructure investments, cycling tracks in particular, and social marketing strategies to alter travel behavior.